Ιστορική εκπαίδευση και χρήση του διαδικτύου: μία διδακτική πρόταση εστιασμένη στις δομικές ιστορικές έννοιες - Καραμανώλη Ελένη (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
The introduction of the Internet in the teaching of History was set in the service of a “New History” in school aiming the historical thinking. Learning through Internet means the collection, evaluation, correlation and handling of the historical information, which is judged absolutely necessary for all new teaching and learning strategies. This History teaching deals with interactive learning in a wide open electronic environment where the teacher takes up a consulting-guiding role. The web and the increasing number of educational software applications consist a powerful tool in the hands of the teacher and contribute in the methodological historical knowledge through searching, gathering, and managing data, the exporting of deductions and finally the sharing of the digital progress. The electronic tools the students will use will assist them handle and conceptualize the structural second order historical concepts such as causation, continuity, change, space, time and empathy. At the beginning of the 21st century students need to have historical and digital literacy in order to deal with the requirements of every day life in a critical way.